2017
DOI: 10.3389/fevo.2017.00160
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Root Mutualists Affect the Predators and Pathogens of Herbivores above Ground: Mechanisms, Magnitudes, and Missing Links

Abstract: Tri-trophic interactions among plants, herbivores, and natural enemies of herbivores are common in nature, and are crucial components of trophic cascades and the dynamics of community composition. Plant traits are key determinants of the interactions between herbivores and their natural enemies aboveground, which in turn are affected by soil organisms. Recent years have seen a surge in studies of the interactions between below-and aboveground biota, including descriptions of how microbial root mutualists influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 133 publications
0
24
0
Order By: Relevance
“…Subsequent studies of other virus-plant-vector species combinations have reported similar findings of virus modification of plant VOCs with enhanced vector attraction to infected plants. This phenomenon has been observed for viruses with different transmission mechanisms including persistently, non-persistently, and semi-persistently transmitted viruses [34,99,102,108,109]. In addition to plant viruses, recent evidence suggests that insect-vectored bacterial pathogens also alter plant olfactory cues to enhance their transmission.…”
Section: Influence Of Pathogenic Microbes On Plant-produced Olfactorymentioning
confidence: 87%
See 1 more Smart Citation
“…Subsequent studies of other virus-plant-vector species combinations have reported similar findings of virus modification of plant VOCs with enhanced vector attraction to infected plants. This phenomenon has been observed for viruses with different transmission mechanisms including persistently, non-persistently, and semi-persistently transmitted viruses [34,99,102,108,109]. In addition to plant viruses, recent evidence suggests that insect-vectored bacterial pathogens also alter plant olfactory cues to enhance their transmission.…”
Section: Influence Of Pathogenic Microbes On Plant-produced Olfactorymentioning
confidence: 87%
“…In this review, we limit our discussion of beneficial plant-associated microbes to their influence on herbivore foraging and oviposition. For a recent review of how beneficial plant-associated microbes alter insect predator and parasitoid behavior, see [34].…”
Section: Beneficial Plant-associated Microbesmentioning
confidence: 99%
“…Beneficial soil microbes such as AM fungi are able to alter plant-insect herbivore interactions through several mechanisms, eliciting changes in the availability and quality of plant nutrients, defensive strategies, and stress tolerance [15]. In addition, AM fungi can affect insect herbivores aboveground, both by changing host-plant quality from the bottom-up [13,16,17] and the resistance of insect herbivores to their natural enemies from the top-down [12,18,19]. During the early developmental stages of the symbiosis, plant defense responses are modulated to facilitate AM fungal colonization of roots, which then leads to activation of plant immune responses both at the local level and throughout the plant [17].…”
Section: Introductionmentioning
confidence: 99%
“…In terrestrial ecosystems, both top-down and bottom-up forces travel with ease across the traditional soil "boundary, " with plants connecting the interactions that occur between above and belowground organisms (van der Putten et al, 2001;van Dam and Heil, 2011;Hunter, 2016). As a result, soil organisms that are associated with plant roots have the potential to affect herbivore populations above ground both by affecting plant quality for herbivores from the bottom-up (Hartley and Gange, 2009;Koricheva et al, 2009;Jung et al, 2012) and the resistance of herbivores to their natural enemies from the top down (Gange et al, 2003;Rasmann et al, 2017;Tao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rootassociated microbes, such as AMF, affect herbivore-natural enemy interactions indirectly by altering plant phenotype (Rasmann et al, 2017;Tao et al, 2017). For instance, AMF increase the attractiveness of plants to natural enemies by changing the volatile emissions of their host plants (Guerrieri et al, 2004;Fontana et al, 2009;Hoffmann et al, 2011;Schausberger et al, 2012;Babikova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%